Diet-Induced Non-alcoholic Fatty Liver Disease and Associated Gut Dysbiosis Are Exacerbated by Oral Infection - Simas, Alexandra M.; Kramer, Carolyn D.; Genco, Caroline A. (Frontiers in Oral Health, 2022)
Increasing evidence indicates that chronic inflammation due to periodontal disease is associated with progression of non-alcoholic fatty liver disease (NAFLD) caused by a Western diet. NAFLD has also been associated with oral infection with the etiological agent of periodontal disease, Porphyromonas gingivalis. P. gingivalis oral infection has been shown to induce cardiometabolic disease features including hepatic lipid accumulation while also leading to dysbiosis of the gut microbiome. However, the impact of P. gingivalis infection on the gut microbiota of mice with diet-induced NAFLD and the potential for those changes to mediate NAFLD progression has yet to be determined. In the current study, we have demonstrated that P. gingivalis infection induced sustained alterations of the gut microbiome composition and function, which was associated with the promotion of NAFLD in steatotic mice. Reduced abundance of short-chain fatty acid-producing microbiota was observed after both acute and chronic P. gingivalis infection. Collectively, our findings demonstrate that P. gingivalis infection produces a persistent change in the gut microbiome composition and function that promotes steatosis and metabolic disease.